The Role of Wind Farms in Estimating Energy Demand in a Microgrid - Semion PELESKOV; Ana-Maria-Ruxandra RESCANU; Mihai REBENCIUC (Communications of International Proceedings, 2020)
The management and control of renewable resources through smart networks represent the future of technology and sustainable development. This paper conducts a study on monitoring the structural health of Smart Grids, more exactly of its nodes - Micro Grids. The main purpose of the research is the estimation of energy demand by modeling the wind speed distribution, determining the power and energy production of the wind turbine. Thus, the Weibull distribution with two parameters, scale parameter and shape parameter, was used in the sense of nonlinear control of the probabilistic wind speed distribution. Using the Maximum Likelihood Method and an algorithm coded in Python, each value in the reference range of the shape parameter was assigned corresponding values of the scale parameter for the two human settlements. Subsequently, by applying the Grammatical Evolution algorithm, which implies a context-free grammar, the best relation which depends on the environmental variables for the scale parameter was obtained. In the future, we intend to improve the nonlinear control of the statistical distribution by completing the Grammatical Evolution algorithm and adding the location parameter in the Weibull distribution.
Keywords: Micro Grid; Wind energy; Weibull distribution; Grammatical Evolution.